Experience of stigma and discrimination reported by people experiencing the first episode of schizophrenia and those with a first episode of depression: The FEDORA project. (August 2015) - Corker, Elizabeth A; Beldie, Alina; Brain, Cecilia; Jakovljevic, Miro; Jarema, Marek; Karamustafalioglu, Oguz; Marksteiner, Josef; Mohr, Pavel; Prelipceanu, Dan; Vasilache, Anamaria; Waern, Margda; Sartorius, Norman; et al.
Aim: To record and measure the nature and severity of stigma and discrimination experienced by people during a first episode of schizophrenia and those with a first episode of major depressive disorder. Methods: The Discrimination and Stigma Scale (DISC-12) was used in a cross-sectional survey to elicit service user reports of anticipated and experienced discrimination by 150 people with a diagnosis of first-episode schizophrenia and 176 with a diagnosis of first-episode major depressive disorder in seven countries (Austria, Croatia, Czech Republic, Poland, Romania, Sweden and Turkey). Results: Participants with a diagnosis of major depressive disorder reported discrimination in a greater number of life areas than those with schizophrenia, as rated by the total DISC-12 score ( p  = .03). With regard to specific life areas, participants with depression reported more discrimination in regard to neighbours, dating, education, marriage, religious activities, physical health and acting as a parent than participants with schizophrenia. Participants with schizophrenia reported more discrimination with regard to the police compared to participants with depression. Conclusion: Stigma and discrimination because of mental illness change in the course of the mental diseases. Future research may take a longitudinal perspective to better understand the beginnings of stigmatisation and its trajectory through the life course and to identify critical periods at which anti-stigma interventions can most effectively be applied.